Physiological and biochemical characterization cellulolytic bacteria - Bharambe, S. D.; Kumar, Kunvar Gyanendra; Singh, R. P.; Pawar, A. S. (International Journal of Environment, Agriculture and Biotechnology, 2024)
Several efficient cellulase producing microorganisms were isolated. The purpose was to identify and characterize those isolates displaying the greatest cellulase activity for the possible use in the large scale biorefining. Cellulases are inducible enzymes that are synthesized by a large number of microorganisms during their growth on cellulosic materials. Cellulases have attracted much interest because of the diversity of their applications. Cellulases are used in the various industrial process, including textile and laundry, food, feed, leather, pulp and paper. The biochemical characterizations of the isolated Bacterial strains from termite gut. .Isolated strains are efficient namely TG I and TG II. Indicate that they may play a role in cellulose digestion in termite gut.